KAJIAN IMPLEMENTASI PERDA INISIATIF DAN EKSEKUTIF KABUPATEN SITUBONDO TAHUN 2018 - Vita Novianti (ACTON, 2018)
The purpose of this study is to find out the Implementation of Regional Initiative and Executive Regulations and describe the factors that become supporters and inhibitors of the Implementation of Initiative and Executive Local Regulations in Situbondo Regency. This research approach uses qualitative research conducted through observation and interviews. Determination of informants in this study using purposive sampling and snowball sampling techniques, so that there are key informants and supporting informants. There is a distinction in the process of drafting until the implementation between the Regulatory Initiative and the Regional Regulations proposed by the Regent. Several factors were the causes of the different process of drafting the Regional Regulation in Situbondo District